1964
DOI: 10.1002/anie.196402771
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Thioketones

Abstract: The methods described in the literature for the synthesis of aliphatic thioketones are examined critically in the light of the authors' own work; new practical methods ofpreparation are reported, and characteristic properties a f thioketones are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…In addition, the rigid structure of 2 which would facilitate stereochemical reasoning, its ready availability in both enantiomeric forms, and the ease with which substituents can be introduced at many positions in stereospecific ways suggested that an investigationof its use as a CDA in glycinate alkylations would prove in~tructive.~ Because of the hindered nature of the carbonyl in 2a, its condensation with amines is known ( 5 ) to be a difficult reaction \ , requiring vigorous reaction conditions. However, prior conversion into the thione 26 (6) markedly increases the facility of "carbonyl" additions (7). For derivatization with glycine esters, the use of 26 appears to be mandatory, as we hatebeen unable to effect such condensations with 2 a under a number of conditions.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, the rigid structure of 2 which would facilitate stereochemical reasoning, its ready availability in both enantiomeric forms, and the ease with which substituents can be introduced at many positions in stereospecific ways suggested that an investigationof its use as a CDA in glycinate alkylations would prove in~tructive.~ Because of the hindered nature of the carbonyl in 2a, its condensation with amines is known ( 5 ) to be a difficult reaction \ , requiring vigorous reaction conditions. However, prior conversion into the thione 26 (6) markedly increases the facility of "carbonyl" additions (7). For derivatization with glycine esters, the use of 26 appears to be mandatory, as we hatebeen unable to effect such condensations with 2 a under a number of conditions.…”
Section: Introductionmentioning
confidence: 88%
“…The 2,l-benzisothiazole 3b should be further sulfurized under the conditions of the reaction to 3 -methyl -7'-thioacetyl-2,l-benzisothiazole ( 3 4 , but this is probably readily hydrolyzed back to 3b during the isolation procedure. Certain thiones are reported to undergo such hydrolyses (14). Compounds without substituents capable of interacting with the heterocyclic ring were not sulfurized under the conditions used.…”
Section: S-s-s S-s Smentioning
confidence: 99%
“…[2] Thioketones are more useful and especially the non-enolizable cycloaliphatic representatives are considered as an attractive class of substrates for studies focused on the reactivity of the C=S group. [3] One of the most remarkable features of thioketones is their excellent reactivity as dipolarophiles observed in [3+2] cycloadditions with 1,3-dipoles such as diazoalkanes, [4a] nitrones, [4b,c] thiocarbonyl S-sulfides (thiosulfines), [4d,e] and thioA C H T U N G T R E N N U N G carbonyl ylides. [4e] These cycloadditions open a convenient access to diverse five-membered sulfur heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: alkoxyallenes · desulfurization · thiiranes · thioketones · thiophenes attack, which subsequently undergo a [2,3]-sigmatropic rearrangement, yielding the S-adducts as final products. [8] In recent publications, reactions of 1 a with a series of alkyllithiums were described.…”
Section: Introductionmentioning
confidence: 99%